NUANSA-NUANSA SASTRA DALAM TAFSIR HAMKA - Kusnadi Kusnadi (Wardah, 2015)
This research is about literature values and functionson on the interpretation of Al-Azhar, by Hamka. Based on the analysis, it is known that there are some literature forms presented, likes proverbs, rhymes, idioms dan poems. The forms function as advice, parable and soul expression to identify the self, environment, and life phenomenon that the message could be understood by Indonesian Malay society. Therefore, literature is a life inspiration presented in beauty in form of langauge, and becomes the reflection of society culture.